2020
DOI: 10.1080/00365521.2019.1710245
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal gene transcription of ulcerative colitis in endoscopic remission

Abstract: Aim/Objective: Ulcerative colitis (UC) is a chronic inflammatory bowel disease. In UC, a wide range of criteria are used for disease remission, with few studies investigating the differences between disease remission and normal control groups. This paper compares known inflammatory and healing mediators in the mucosa of UC in clinical remission and normal controls, in order to better describe the remission state. Method: Mucosal biopsies from 72 study participants (48 UC and 24 normal controls) were included f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Several reports concerning the molecular background of endoscopic evaluation and clinical outcomes have been published. It has been reported that mRNA expression of mucosal cytokines, such as IL-33, IL-6, and IL-10, was upregulated in patients with an MES of 1 compared to those with an MES of 0 [23]. Although this study did not investigate the relationship between clinical outcome and mucosal cytokine expression, it has been revealed that colonic mucosa diagnosed as MES 1 had a different cytokine pro le than those diagnosed as MES 0.…”
Section: Discussionmentioning
confidence: 67%
“…Several reports concerning the molecular background of endoscopic evaluation and clinical outcomes have been published. It has been reported that mRNA expression of mucosal cytokines, such as IL-33, IL-6, and IL-10, was upregulated in patients with an MES of 1 compared to those with an MES of 0 [23]. Although this study did not investigate the relationship between clinical outcome and mucosal cytokine expression, it has been revealed that colonic mucosa diagnosed as MES 1 had a different cytokine pro le than those diagnosed as MES 0.…”
Section: Discussionmentioning
confidence: 67%
“…Of note, STAT3 is a recognized proinflammatory transcripts. 34 It is known that the differentiation of Th17 cells typically requires the cytokines signaling via the STAT3 transcription activator. 35 STAT3 was upregulated in CD4þ naive T cell of UC and SC, which was also consistent with the change of Th17 cell and IL-17 signal in systemic inflammation.…”
Section: The Th17 Cell Was the Major Immune Characteristic Of Uc But Immunoglobulin A Was The Key Local Immune Component Of Inflamed Tissmentioning
confidence: 99%
“…In the present study, we measured the expression of the genes SMAD7, TNF, TLR2, TNFRSF1B, TBX21, DEFA5, IL11, TREM1, and OSM (previously studied as related to the anti-TNF response or IBD in adults) [25,[27][28][29][30][31] in the whole blood of children with IBD before and after 2 weeks of anti-TNF treatment. The aim was to evaluate whether these genes could be very early pharmacogenomics biomarkers of response to anti-TNF agents in pIBD.…”
Section: Introductionmentioning
confidence: 99%